2022
DOI: 10.1055/a-1830-8716
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Increases the Sensitivity of Osteosarcoma Cells to Chemotherapy Drug Cisplatin

Abstract: Chemotherapy, which is one of the common treatments for osteosarcoma (OS), has many side effects and in some cases has low effectiveness due to chemoresistance, hence it is vital to study new therapies for OS. In this regard, we combined melatonin with cisplatin and evaluate their effect on MG63 OS cells. Since melatonin has anti-cancer properties, we hypothesized that its combination with cisplatin could increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Recently, Hosseini et al linked miR-181b downregulation to the increased sensitivity of osteosarcoma cells to cisplatin following the addition of melatonin to the treatment [56]. Consistent with this observation, our findings indicate that miR-181b-3p is overexpressed in the non-responders group, indicating that this may be attributed to drug resistance.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Hosseini et al linked miR-181b downregulation to the increased sensitivity of osteosarcoma cells to cisplatin following the addition of melatonin to the treatment [56]. Consistent with this observation, our findings indicate that miR-181b-3p is overexpressed in the non-responders group, indicating that this may be attributed to drug resistance.…”
Section: Discussionsupporting
confidence: 90%
“…In the results of the tunnel analysis, it was observed that the melatonin and cisplatin treatments were therapeutically effective on HT-29 cells and increased the number of apoptotic cells. Combined administration of melatonin and cisplatin has been shown to be effective in osteosarcoma cells (16). In our study, the administration of melatonin and/or cisplatin was also found to be more effective when combined to use.…”
Section: Discussionsupporting
confidence: 63%
“…In cases where metastasis has not occurred, the patient's survival rate increases with the removal of the tumor area through surgical intervention [36]. Osteosarcoma typically metastasizes to the lungs, exacerbating the clinical outcomes for patients [37]. The primary factors contributing to the lung metastasis rate of 80-90% in osteosarcoma include tumor-host signaling pathways, the structure of lung epithelial tissue, and innate adaptive immunity [38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is linked to factors such as the consumption of tobacco products, air pollution, and economic inadequacy [40]. Additionally, lung cancer can occur due to the propensity of bone cancer to metastasize to the lung [37].…”
Section: Discussionmentioning
confidence: 99%